PENGARUH PELAYANAN TERHADAP KEPUASAN PASIEN PADA PUSKESMAS TELUK LINGGA DI SANGATTA - Hartini, Nor Saima (EKONOMIA, 2013)
The purpose of this study was to determine the level of patient satisfaction in terms of service include Reliability , Responsiveness , Empathy , Assurance and Real Being provided by health centers in Sengata Linga bay . The experiment was conducted for 3 months ( April to June 2013) at the health center in the Gulf of Sangatta Linga , which bekaitan to influence Patient Satisfaction in service to the research conducted Sangatta.Kegiatan : The study of literature , field observations , interviews , documentation , data collection and analysis . dikupulkan data in the study include : a general overview of cooperative , organizational structure and answer responden.Analisis data using multiple regression analysis with the formula Y = a + b1X1 b2X2 + + + b5X5 b4X4 b3X3 + + e Based on calculations derived regression equation : Y = 0.321 + 0.144 X1 + 0.138 X2 + 0.157 X3 + 0.256 X4 + 0.232 X5 From these equations can be explained that each coefficient b obtained a positive value , it means if each variable studied further enhanced , then one by one will affect patient satisfaction . If the variable reliability ( X1 ) improved by one point , the patient satisfaction increased 0.144 points . If the variable responsiveness ( X2 ) increased one point , the patient satisfaction increased 0.138 points . If the variable empathy ( X3 ) increased one point , then increased patient satisfaction guarantee 0,157 points if the variable ( X4 ) improved by one point , then increased patient satisfaction 0.256 points . If the real form of the variable ( X5 ) improved by one point , the patient satisfaction increased 0.232 points . Based Fhitung = 22.639 > F = 3.405 indicates that the service factor together positive and significant impact on patient satisfaction . Of 5 independent variables studied variables guarantees a greater influence means suitable for use collateral variables predicted Y variables ( patient satisfaction ) at the health center in Sengata Linga bay .